2017
DOI: 10.1158/0008-5472.can-17-1915
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Promote Hepatocarcinogenesis via lncRNA–MUF Interaction with ANXA2 and miR-34a

Abstract: Accumulating evidence suggests that cancer-associated mesenchymal stem cells (MSC) contribute to the development and metastasis of hepatocellular carcinoma (HCC). Aberrant expression of long noncoding RNAs (lncRNA) has been associated with these processes but cellular mechanisms are obscure. In this study, we report that HCC-associated mesenchymal stem cells (HCC-MSC) promote epithelial-mesenchymal transition (EMT) and liver tumorigenesis. We identified a novel lncRNA that we termed (MSC-upregulated factor) th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
168
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(172 citation statements)
references
References 47 publications
4
168
0
Order By: Relevance
“…The functional role of a lncRNA depends on the downstream molecules that it regulates, including the miRNAs it affects in its function as a ceRNA. The lncRNA mesenchymal stem cells‐upregulated factor (MUF) functions as a ceRNA of miR‐34a to regulate Snail1 activity and modulate hepatocellular carcinoma (HCC) progression . The lncRNA HOXD‐AS1 is upregulated in HCC tissues and competitively binds miR‐130a‐3p, regulating EZH2 and MMP2 expression and facilitating HCC metastasis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional role of a lncRNA depends on the downstream molecules that it regulates, including the miRNAs it affects in its function as a ceRNA. The lncRNA mesenchymal stem cells‐upregulated factor (MUF) functions as a ceRNA of miR‐34a to regulate Snail1 activity and modulate hepatocellular carcinoma (HCC) progression . The lncRNA HOXD‐AS1 is upregulated in HCC tissues and competitively binds miR‐130a‐3p, regulating EZH2 and MMP2 expression and facilitating HCC metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA mesenchymal stem cells-upregulated factor (MUF) functions as a ceRNA of miR-34a to regulate Snail1 activity and modulate hepatocellular carcinoma (HCC) progression. 29 The lncRNA HOXD-AS1 is upregulated in HCC tissues and competitively binds miR-130a-3p, regulating EZH2 and MMP2 expression and facilitating HCC metastasis. 30 By online software prediction, we found the possibility of the existence of the OIP5-AS1/miR-129-5p/ SOX2 axis.…”
Section: Discussionmentioning
confidence: 99%
“…We identified a known lung cancer‐related lincRNA LINC00941 and four novel lincRNA‐based prognostic biomarkers, namely, LINC00578 , TDRKH‐AS1, RBPMS‐AS1 and RP11‐470 M17.2 in LUAD patient samples. LINC00941 was reported to promote mesenchymal stem cells to hepatocarcinogenesis, whose high expression in LUAD was associated with poorer OS of LUAD patients (FDR = 7.7e‐07). The association between LINC00941 and lung cancer was supported by previous findings that LINC00941 act as a robust prognostic classifier in stage I LUAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…GS is a target of the Wnt/beta‐catenin signal pathway in the liver, and the expression of GS is regulated by translocation of beta‐catenin from the cytoplasm to the cell nucleus, which indicates the activation of the Wnt/beta‐catenin signal pathway . Recently, studies have shown that activation of this pathway contributes to carcinogenesis and epithelial–mesenchymal transition (EMT) in HCC . Therefore, it is logical to speculate that GS might play a critical role in HCC progression.…”
Section: Introductionmentioning
confidence: 99%